SPATIAL CLUSTER ANALYSIS OF NEW AND RELAPSED CASES OF PULMONARY TUBERCULOSIS BY DISTRICT: PAKISTAN 2015 - Shaikh, Masood Ali; Malik, Naeem Abbas (Journal of Ayub Medical College Abbottabad, 2019)
Tuberculosis (TB) is a major public health problem in Pakistan. There are no studies in Pakistan on TB disease mapping and spatial analysis at the country level. This study was conducted to map and identify clusters of TB incidence rates at the district level for all provinces of Pakistan, including Islamabad for all new and relapsed cases of pulmonary TB, for the year 2015. The district level TB rate for new and relapsed cases ranged from 4.7 to 422.6 per 100,000. Global Moran's I was 0.25238, with a pseudo p-value of 0.001, indicating clustering in the data. Local Moran's I, i.e., Local indicators of Spatial Association identified 11 districts as high-high clusters, and 20 districts as low-low clusters. Better understanding of these hot and cold spot districts would be helped by the availability and analysis of TB data at the more granular level of Union Councils in the country. Keywords: Tuberculosis; Epidemiology; GIS; Pakistan